Computer Crimes Act 1997 v Computer Misuse Act 1993: the effectiveness in curbing hackers / Effa Suzieana Zainal, Nor Haslina Ismail and Nur Asyikin Mansoor. - Zainal, Effa Suzieana; Ismail, Nor Haslina; Mansoor, Nur Asyikin (2007)
This research is done to enlighten the Malaysian and Singaporean society about the danger and effects of computer crime towards them. As we already know the proliferation of computer technology into every aspect of society has led to computer crime activities, especially hacking. Therefore, we feel that there is a need to get a real understanding on hacking as one type of computer crimes and the effectiveness of the prevention that had been provided in both countries. This research is done to critically analyzing the standards of security measures that need to be taken to curb hacking, in addition to the existing local law enforcement on cyber law in both Malaysia and Singapore. This research also discuss the various offences fall under cyber crime and within the law enforcement agencies, how a set of rules such as statute must be developed to address the various categories of computer crime. Besides that, we also discuss the possible challenges faced by Malaysian and Singaporean enforcers in dealing with this crime. On the other hand, we have also done a research regarding the issues on whether there is any international convention to harmonize laws in regards to cyber crime offences and whether it is applicable to each state. As a conclusion, cooperation between the countries is needed in order to prevent hacking. This is proven by the effective steps taken by the two countries in dealing with computer crime.